PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN SIKAP TOLERANSI DAN PRESTASI BELAJAR - Reni Ariani; Bambang Sahono (UNIB Press, 2022)
This study aims to increase the attitude of tolerance and learning achievement of students in the science subjects of class VIII SMP Negeri 8 Pagar Alam. The types of research used are Classroom Action Research (CAR) and Quasi-Experimental Research. The subjects of this study were students of class VIII SMP Neeri 8 Pagar Alam. The sample of PTK class is class VIII.A, the sample of the experimental class is class VIII.C and the sample of the control class is class VIII.B. The data collection technique used in this study was an observation assessment sheet and student test results. The data in this study were then analyzed using mean, percentage and t-test. The results showed that the application of the Teams Games Tournament type of cooperative learning model can increase students' tolerance and learning achievement and the implementation of the Teams Games Tournament type of cooperative learning model is effective in improving the learning achievement of eighth grade students of SMP Negeri 8 Pagar Alam.